1986
DOI: 10.1073/pnas.83.15.5355
|View full text |Cite
|
Sign up to set email alerts
|

Molecular devices: Caroviologens as an approach to molecular wires—synthesis and incorporation into vesicle membranes

Abstract: Molecular wires, which would allow electron flow to take place between different components, are important elements in the design of molecular devices. An approach to such species would be molecules possessing an electron-conducting conjugated chain, terminal electroactive polar groups, and a length sufficient to span a lipid membrane. To this end, bispyridinium polyenes of different lengths have been synthesized and their incorporation into the bilayer membrane of sodium dihexadecyl phosphate vesicles has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
2

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(55 citation statements)
references
References 25 publications
0
53
0
2
Order By: Relevance
“…From Finally, the structural and physical features of the present and related species may be of use in the design of molecular devices (30), taking advantage of cooperativity and selfassembly processes.…”
Section: Resultsmentioning
confidence: 99%
“…From Finally, the structural and physical features of the present and related species may be of use in the design of molecular devices (30), taking advantage of cooperativity and selfassembly processes.…”
Section: Resultsmentioning
confidence: 99%
“…charge carrier conducting rods, into lipid membranes is possible due to the fact that  interactions can stabilize the trans-membrane orientation of the bolapolyphiles in the bilayer. This is of wider interest for molecular electronics in well-organized hybrid-and superstructures [43][44][45][46][47] , especially for the addressing of cells by external electrical signals as required in devices coupling sensors, stimulators or chips with living cells or protocells. [48][49] …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that conjugated systems with appropriate end groups (3)(4)(5) and confined aromatic systems (6) can transfer excitations upon photon absorption or after reduction or oxidation. A major challenge is to achieve charge transfer with low fields as in metallic wires and to establish communication with individual, electrically separated nanometer structures or molecules.…”
mentioning
confidence: 99%